Field resistance to wheat stem rust in durum wheat accessions deposited at the USDA National Small Grains Collection. Issue 4 (30th May 2021) - Olivera, Pablo D.; Bulbula, Worku D.; Badebo, Ayele; Bockelman, Harold E.; Edae, Erena A.; Jin, Yue
Abstract: Wheat stem rust, caused by Puccinia graminis f. sp. tritici, is a re‐emerging disease, posing a significant threat to durum wheat production worldwide. The limited number of stem rust resistance genes in modern cultivars compels us to identify and incorporate new effective genes in durum wheat breeding programs. We evaluated 8, 245 spring durum wheat accessions deposited at the USDA National Small Grains Collection (NSGC) for resistance in field stem rust nurseries in Debre Zeit, Ethiopia and St. Paul, MN (USA). A higher level of disease development was observed at the Debre Zeit nursery compared with St. Paul, and the effective alleles of Sr13 in this nursery did not display the level of resistance observed at the St. Paul nursery. Four hundred and ninety‐one (∽6%) accessions exhibited resistant to moderately susceptible responses after three field evaluations at Debre Zeit and two at St. Paul. Nearly 70% of these accessions originated from Ethiopia, Mexico, Egypt, and USA. Eight additional countries, namely Portugal, Turkey, Italy, Canada, Chile, Australia, Syria, and Tunisia contributed to 19% of the resistant to moderately susceptible entries. Among the 491 resistant to moderately susceptible accessions, 53.8% (n = 265) were landraces, and 28.4% (n = 139) and 11.4% (n = 55) were breeding lines and cultivars, respectively. Breeding lines and cultivars displayed a higher level and frequency of resistance than the landraces. We concluded that a large number of durum wheat accessions from diverse origins deposited at the NSGC can be exploited for diversifying and improving stem rust resistance in wheat. Core Ideas: Identify new sources of stem rust resistance through field evaluations of durum wheat. 8, 245 durum accessions deposited at NSGC evaluated in two field nurseries (Ethiopia and US). Presence of large number of entries from diverse origin that can be used for rust resistance.